Review of the monograph by Astafyev A.E., Bogdanov E.S. Burial and memorial assemblage Altynkazgan (III – the first half of the VI century AD). Almaty, 2023. 384 p. - Sergey G. Botalov; Ilya E. Lyubchansky (Археология евразийских степей)
In 2023, the monograph " The burial and memorial complex of Altynkazgan (III – the first half of the VI century AD)" was published, prepared by a research fellow at the Margulan Institute of Archaeology A.E. Astafyev and a senior research fellow at the Institute of Archaeology and Ethnography of the Siberian Branch RAS E.S. Bogdanov. The presented book belongs to the category of works that mark the emergence of a certain epochal phenomenon and the manifestation of historical patterns that were previously blank spots on the historical map of Eurasia. The result of almost ten years of field works in extreme natural and climatic conditions led to new civilization-wide discoveries. The period of late Antiquity and early Middle Ages in the Ural-Kazakhstan steppes, as it is known, was, figuratively speaking, a kind of "vague" incomprehensible – unstudied time. This edition reveals an impressive picture of the historical and cultural communications and cult and religious beliefs of the nomadic and semi-nomadic population of the large region of Western Kazakhstan, Khwarazm and Central Asian interfluve.